2014
DOI: 10.1007/978-1-4614-3209-8_39
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cone Density in a Japanese Macaque (Macaca fuscata) Model of Age-Related Macular Degeneration with Commercially Available Adaptive Optics

Abstract: The aim of this study was to assess the feasibility of using a commercially available high-resolution adaptive optics (AO) camera to image the cone mosaic in Japanese macaques (Macaca fuscata) with dominantly inherited drusen. The macaques examined develop drusen closely resembling those seen in humans with age-related macular degeneration (AMD). For each animal, we acquired and processed images from the AO camera, montaged the results into a composite image, applied custom cone-counting software to detect ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Thus, developing nonhuman primate models with more advanced stages of AMD may require long-term dietary and environmental modifications that better represent human behavior. Interestingly, Japanese macaques (Macaca fuscata) have an early-onset form of drusen with a dominant mode of inheritance 42 . Cynomologus macaques (Macaca fascicularis) also develop drusen in an age-dependent manner with a potential link to hematologic markers 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, developing nonhuman primate models with more advanced stages of AMD may require long-term dietary and environmental modifications that better represent human behavior. Interestingly, Japanese macaques (Macaca fuscata) have an early-onset form of drusen with a dominant mode of inheritance 42 . Cynomologus macaques (Macaca fascicularis) also develop drusen in an age-dependent manner with a potential link to hematologic markers 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies reported a high prevalence of drusenoid pathology (30%-74%) in free-ranging rhesus macaques (Macaca mulatta) from Cayo Santiago in Puerto Rico, [8][9][10][11] whereas other colonies within the continental United States have shown variable prevalences (5%-47%), likely due to differences in environmental conditions, diet, and genetic background. [12][13][14][15] Cynomolgus and Japanese macaques (Macaca fascicularis and Macaca fuscata) also exhibit an early onset form of the disease with a dominant mode of inheritance, [16][17][18][19][20][21] but the precise genetic basis remains unclear. 20 Rhesus monkeys with drusenoid lesions share genetic polymorphisms in the age-related maculopathy susceptibility 2 (ARMS2) locus with human patients with AMD [22][23][24] and demonstrate similar protein components within the drusen lesions, 19 suggesting common mechanisms between drusen formation in humans and nonhuman primates.…”
mentioning
confidence: 99%
“…The concept of a visual fovea is well known. The density of cones in the retina of the eye peaks as we approach the center of the back of the eye [5,33,42]. This foveation gives us high acuity in our central vision.…”
Section: Biological Inspiration Foveation In Visionmentioning
confidence: 99%